HIV-1 vaccines: let's get physical. - Goonetilleke, N; McMichael, A (Cell Press, 2013)
Ferguson et al. (2013) use applied physics to quantitate the fitness of HIV-1 Gag based on sequence variability across the protein. This enables a new approach to vaccine design that focuses CD8+ T cell responses on fitness-constrained parts of Gag.